Color‐Temperature Tuning and Control of Trichromatic White Light Emission from a Multisegment ZnCdSSe Heterostructure Nanosheet. (4th October 2016) - Turkdogan, Sunay; Fan, Fan; Ning, Cun‐Zheng
Abstract : Tuning and control of color temperature of trichromatic white light emission is demonstrated for the first time from a single ZnCdSSe nanosheet realized by a novel growth method using chemical vapor deposition (CVD). The nanosheets have thicknesses in the range of 60–350 nm and lateral dimensions of tens of micrometers. These nanosheet structures with three or more parallel segments are able to emit the three primary colors of light from a monolithic body and the combination of the emitted light appears as white. Due to temperature dependence of the alloy composition and the spatial profile of the temperature in the CVD chamber, alloy compositions and the widths of individual segments can be controlled by the substrate locations and the growth time, respectively. Such control determines the emission color and relative intensity of each segment, thus resulting in the tuning of the color temperature of the white light, or in the realization of any visible colors. Trichromatic white light emission is demonstrated with the correlated color temperature covering an extensive range from 2700 to 14 400 K using various growth parameters. In addition, a dynamic tuning of colors and color temperature is demonstrated by sweeping a pump beam across a single nanosheet. Abstract : Tuning and control of the color temperature of white light emission from a monolithic heterostructure nanosheet is demonstrated. Correlated color temperature tunable between 2700 and 14400 K is achieved using a simple but versatile growth method. Additionally, dynamical tuning of colors is demonstrated by adjusting the relative pumping power of each segment via a simple laser beam sweeping method.